Digging into lorlatinib resistance in ALK-positive lung cancer: an editorial - Facchinetti, Francesco; Tiseo, Marcello (Chinese Clinical Oncology; Vol 8, Supplement 1 (October 22, 2019): Chinese Clinical Oncology, 2018)
Non-small cell lung cancers (NSCLC) harboring molecular oncogenic activations (e.g., EGFR, MET, BRAF mutations, ALK, ROS1 fusions) represent a peculiar subgroup of disease. Indeed, the availability of targeted agents deeply impacts on the prognosis of patients suffering from these tumors. Moreover, the sequential administration of specific inhibitors allows more and more prolonged survival (1-5). Besides EGFR-driven lung cancers, depending on the detection of T790M mutation to switch to osimertinib when resistance to first-line targeted therapy occurs, ALK-positive disease is an emblematic example of the clinical success of sequential inhibitors (6).